Substitusi Tepung Sagu Dan Tepung Daun Kelor Terhadap Kualitas Organoleptik Bakso Daging Ayam - Walten, Theofilus; Liur, Isye Jean; Tiven, Nafly Comilo (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to determine the substitution of sago flour with moringa leaf flour on the organoleptic quality of chicken meatballs. Meatballs are made with the composition of 35% chicken breast, 45% sago flour, 10% ice cubes, 5% garlic, 3% salt, and 2% pepper/pepper. Sago flour is substituted with Moringa leaf flour, with a level of 5%, 10%, and 15%. The chicken meat is ground with 5% ice cubes, added with sago flour, spices, and 5% ice cubes, then mixed until homogeneous. The dough is formed into rounds (± 2 cm), then boiled in boiling water until cooked (until the meatballs float), then removed, drained, cooled, and prepared for the organoleptic test. The organoleptic test was performed using 25 untrained panelists. The variables observed were the color, smell, firmness, texture, and taste of the meatballs. The data obtained were analyzed for variance with a completely randomized design with 4 treatments, namely P0 (0% moringa leaf flour), P1 (5% moringa leaf flour), P2 (10% moringa leaf flour), P3 (15% moringa leaf flour). If there are differences between treatments, further tested with Duncan's test. The results of the statistical analysis showed that sago flour substituted with moringa leaf flour significant effect on the color, smell, firmness, texture, and taste of chicken meatballs.